Challenges of family caregivers of children with special needs of multiple, complex and continuing care at home - Beatriz Caroline Dias; Sueli MutsumiTsukuda Ichisato; Maria Angelica Marchetti; Eliane Tatsch Neves; Ieda Harumi Higarashi; Sonia Silva Marcon (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To describe the challenges of family caregivers of children with special needs of multiple, complex and continuing care at home. Methods: Qualitative study based on the theoretical framework of the Patient and Family-Centerd Care (PFCC). We interviewed eleven family caregivers from 13 children enrolled in a special school in the Brazilian city of Maringá (PR). The data were subject to content analysis, thematic modality. Results: The main challenges identified are the lack of preparation for home care, the difficulty of access and follow-up in Primary Health Care services, and the difficulty of including the child in social interaction. However, caregivers react positively to these adversities. Conclusions and implications for practice: The nurses need the necessary training to transcend hospital technical care and to develop a care practice based on family-centerd care, considering this as a protagonist, including it in the process for the quality of life of these children.